DIPG-25. Patterns of cerebrospinal fluid diversion and survival in children with diffuse intrinsic pontine glioma: a report from the International Diffuse Intrinsic Pontine Glioma Registry. (3rd June 2022) - Cooney, Tabitha; DeWire-Schottmiller, Mariko; Lane, Adam; Saab, Raya; Bandopadhayay, Pratiti; Dorris, Kathleen; Packer, Roger; Kilburn, Lindsay; Minturn, Jane; Dodgshun, Andrew; Parkin, Sara; Goldman, Stewart; et al.
Abstract: BACKGROUND: There are no standard practice guidelines for cerebrospinal (CSF) diversion for diffuse intrinsic pontine glioma (DIPG), nor clear understanding of potential for palliation and life-prolongation. We evaluated CSF diversion characteristics in children with DIPG to determine incidence, indications, symptom effects, and survival. METHODS: Data were extracted from subjects registered in the International DIPG registry (IDIPGR). Univariable analyses was performed using the Fisher's exact test or Wilcoxon rank sum test. Survival was estimated using the Kaplan-Meier method. RESULTS: Evaluable patients (n=542) met criteria for DIPG diagnosis by central radiologic review; of those, 126 (23%) had permanent CSF diversion. Median time from diagnosis to diversion was 0.5 months (IQR 0.1-4.5 months). Those with permanent diversion were significantly younger (median 5.4 years vs 7.0 years, p<0.001) and had higher incidence of hydrocephalus at diagnosis (65.3% vs 11.9%, p<0.001). Permanent CSF diversion did not significantly impact overall survival (OS) (p=0.4), even amongst the 124 patients with hydrocephalus at presentation (p=0.20). Those with permanent diversion prior to radiation therapy demonstrated longer median OS than those in whom diversion was placed after radiation (14.3 vs 9.6 months, p=0.001). Patients reported significantly less headache and vomiting at last follow up after permanent CSF diversion compared to pre-diversion (p<0.0001 and p=0.001, respectively), however steroid use was also significantly higher at last follow-up after CSF diversion (p<0.001). CONCLUSIONS: Amongst an international cohort, DIPG patients who had permanent CSF diversion were significantly younger and had higher rates of hydrocephalus at initial presentation than those without permanent diversion. Symptoms of increased intracranial pressure improved in those with CSF diversion, although a direct effect may be confounded by increased steroid use. Permanent CSF diversion did not prolong overall survival in this large cohort of patients, even amongst those who presented with hydrocephalus.